0018 Sleep Difficulty and Weekly Sedentary Minutes. (25th May 2022) - Marshall, Joseph; Mason, Brooke; Wills, Chloe; Tubbs, Andrew; Grandner, Michael
Abstract: Introduction: Decreased energy and activity may be a mechanism linking poor sleep health and cardiometabolic risk. This study aimed to examine, at the national level, whether poor sleep quality was associated with more sedentary time (as opposed to less exercise, which has been difficult to establish). Methods: Data from the 2017 - March 2020 National Health and Nutrition Examination Survey was used. A linear regression analysis was completed to assess the relationship between sedentary minutes and self-reported sleep difficulties. These were assessed by self-report of difficulty "falling asleep, staying asleep, or sleeping too much" over the past 2 weeks, with options for "never, " "less than half the days, " "more than half the days" and "almost always." Covariates included sex, age, race/ethnicity, education level, and relationship status. Results are unweighted; weighted results are forthcoming. Results: All groups experiencing self-reported sleep difficulties demonstrated increased sedentary minutes when compared to those that do not experience sleep difficulties. More specifically, unadjusted results show 21.5 more sedentary minutes (B: 21.5, [95%CI:10.8, 32.2], p<0.001) for those that have sleep problems several days a week, 21.8 more sedentary minutes (B:21.8, [95%CI:4.90, 38.7], p<0.001) for those that have sleep difficulties more than half the days in a week, and 42.3 minutes (B: 42.3, [95%CI:26.8, 57.8], p<0.001) for those that have sleep difficulties nearly every day during the week. Once adjusted for covariates, results showed 17.6 more sedentary minutes (B:17.6, [95%CI:6.76, 28.3], p<0.001) for those that have sleep difficulties several days a week, 18.3 more minutes (B:18.3, [95%CI:1.45, 35.1], p<0.001) for those that have sleep difficulties more than half the days in a week, and 48.4 more sedentary minutes (B:48.4, [95%CI:32.8, 63.9], p<0.001) for those that have sleep difficulties nearly every day during the week. Conclusion: Those with general sleep difficulties were more likely to report more sedentary minutes per day. Although previous efforts have focused on improving physical activity directly, perhaps future efforts could target sleep health as a way to reduce sedentary behavior. Support (If Any):